Produksi Media Dan Dampaknya Pada Perubahan Sosial Dan Politik Di Masyarakat Studi Deskriptif Tayangan CNN Indonesia Pada Pemberitaan K-Pop Diantara Strategi Diplomasi Forum Dunia - Puput Sapinatunajah; Tantan Hermansyah; Nasichah Nasichah (CV. ITTC INDONESIA, 2022)
Television is a communication medium that has an important role in shaping people's attitudes and personalities. There are three stages in the production process, namely pre-production, production and post-production. Effect is an important element in the whole communication process. The presence of the Korean entertainment industry in world forums also shows the concern of young people in the social and political world. Referring to this background, this study aims to answer major and minor questions. The major question is, How is media production and its impact on social and political changes in society? While the minor question is what is the reason for the media reporting the news? Why does this news have an impact? What are the reactions of the audience or the public to the news? In this study using the theoretical basis of Dennis McQuail. In the effect theory chapter (Dennis McQuail, 2011: 212) says media effect is a consequence of what the mass media do, whether intentional or not. CNN Indonesia raises a story based on an issue that is developing in society. and much discussed both offline and online through the mass media. In Korea, BTS is appointed as the country's envoy in public diplomacy. BTS's speech at the trial was considered very influential for young people. In several countries it has become school subject matter in three countries, namely South Korea, Singapore and Vietnam. Â